Potential active materials for photo-supercapacitor: a review - Ng, C. H.; Lim, Hong Ngee; S., Hayase; I., Harrison; A., Pandikumar; Huang, N. M. (Elsevier, 2015)
The need for an endless renewable energy supply, typically through the utilization of solar energy in most applications and systems, has driven the expansion, versatility, and diversification of marketed energy storage devices. Energy storage devices such as hybridized dye-sensitized solar cell (DSSC)–capacitors and DSSC–supercapacitors have been invented for energy reservation. The evolution and vast improvement of these devices in terms of their efficiencies and flexibilities have further sparked the invention of the photo-supercapacitor. The idea of coupling a DSSC and supercapacitor as a complete energy conversion and storage device arose because the solar energy absorbed by dye molecules can be efficiently transferred and converted to electrical energy by adopting a supercapacitor as the energy delivery system. The conversion efficiency of a photo-supercapacitor is mainly dependent on the use of active materials during its fabrication. The performances of the dye, photoactive metal oxide, counter electrode, redox electrolyte, and conducting polymer are the primary factors contributing to high-energy-efficient conversion, which enhances the performance and shelf-life of a photo-supercapacitor. Moreover, the introduction of compact layer as a primary adherent film has been earmarked as an effort in enhancing power conversion efficiency of solar cell. Additionally, the development of electrolyte-free solar cell such as the invention of hole-conductor or perovskite solar cell is currently being explored extensively. This paper reviews and analyzes the potential active materials for a photo-supercapacitor to enhance the conversion and storage efficiencies.